2013
DOI: 10.7567/jjap.52.116504
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of In0.68Ga0.32As Thermophotovoltaic Device Grown on Compositionally Nonmonotonically Graded InAsP Buffer by Metal–Organic Chemical Vapor Deposition

Abstract: An In0.68Ga0.32As thermophotovoltaic (TPV) cell on a compositionally nonmonotonically graded InAsP buffer with a band gap energy of 0.60 eV grown by metal–organic chemical vapor deposition (MOCVD) has been fabricated. The performance of the TPV device was greatly improved with optimized material growth, the use of an absorption layer of suitable width, and appropriate TiO2/SiO2 antireflective coating design. Under standard AM1.5G spectra, the open circuit voltage (V oc) increases from 0.19 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…The effect of different buffer structures, such as a single buffer layer, compositionally graded buffer layers and superlattice buffer layers, were investigated [156,[167][168][169]. A lattice mismatch of ∼1.2% was introduced between In 0.68 Ga 0.32 As and a compositionally nonmonotonically graded InAsP buffer layer (14 layer grades) [155,156]. On the other hand, Hudait et al [85,91] has grown In 0.69 Ga 0.31 As using the MBE method and reported a 1.1% lattice-mismatch between the device layer and the InP substrate.…”
Section: Performance Of Ingaas-based Tpv Cellmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of different buffer structures, such as a single buffer layer, compositionally graded buffer layers and superlattice buffer layers, were investigated [156,[167][168][169]. A lattice mismatch of ∼1.2% was introduced between In 0.68 Ga 0.32 As and a compositionally nonmonotonically graded InAsP buffer layer (14 layer grades) [155,156]. On the other hand, Hudait et al [85,91] has grown In 0.69 Ga 0.31 As using the MBE method and reported a 1.1% lattice-mismatch between the device layer and the InP substrate.…”
Section: Performance Of Ingaas-based Tpv Cellmentioning
confidence: 99%
“…The vast majority of lattice-matched and mismatched InGaAs TPV structure reported the use of AuGe and Ti/Au as front metal contact and Au and TiAu as back metal contact [ 85 , 102 , 164 ] to produce an ohmic contact. Tan et al [ 155 ] used Ni/AuGe/Ni/Au metallization scheme for n-type ohmic contact, and Pd/Zn/Pd/Au metallization was used for p-type ohmic contact. Recently, Kao et al [ 132 ] reported the utilization of AuGe/Au metallization for n-type InGaAs layer.…”
Section: Ingaas-based Tpv Cellmentioning
confidence: 99%
See 3 more Smart Citations